Effect of intermittent preventive treatment for malaria with dihydroartemisinin-piperaquine on immune responses to vaccines among rural Ugandan adolescents: randomised controlled trial protocol B for the 'POPulation differences in VACcine responses' (POPVAC) programme. Issue 2 (16th February 2021) - Natukunda, Agnes; Nkurunungi, Gyaviira; Zirimenya, Ludoviko; Nassuuna, Jacent; Oduru, Gloria; Amongin, Rebecca; Kabuubi, Prossy N; Mutebe, Alex; Onen, Caroline; Amongi, Susan; Nakazibwe, Esther; Akello, Florence; et al.
Abstract : Introduction: Drivers of lower vaccine efficacy and impaired vaccine-specific immune responses in low-income versus high-income countries, and in rural compared with urban settings, are not fully elucidated. Repeated exposure to and immunomodulation by parasite infections may be important. We focus on Plasmodium falciparum malaria, aiming to determine whether there are reversible effects of malaria infection on vaccine responses. Methods and analysis: We have designed a randomised, double-blind, placebo-controlled, parallel group trial of intermittent preventive malaria treatment versus placebo, to determine effects on vaccine response outcomes among school-going adolescents (9 to 17 years) from malaria-endemic rural areas of Jinja district (Uganda). Vaccines to be studied comprise BCG vaccine on day 'zero'; yellow fever, oral typhoid and human papilloma virus vaccines at week 4; and tetanus/diphtheria booster vaccine at week 28. Participants in the intermittent preventive malaria treatment arm will receive dihydroartemisinin/piperaquine (DP) dosed by weight, 1 month apart, prior to the first immunisation, followed by monthly treatment thereafter. We expect to enrol 640 adolescents. Primary outcomes are BCG-specific interferon-γ ELISpot responses 8 weeks after BCG immunisation and for other vaccines, antibody responses to key vaccine antigens at 4 weeks after immunisation. In secondary analyses, we will determine effects of monthly DP treatment (versus placebo) on correlates of protective immunity, on vaccine response waning, on whether there are differential effects on priming versus boosting immunisations, and on malaria infection prevalence. We will also conduct exploratory immunology assays among subsets of participants to further characterise effects of the intervention on vaccine responses. Ethics and dissemination: Ethics approval has been obtained from relevant Ugandan and UK ethics committees. Results will be shared with Uganda Ministry of Health, relevant district councils, community leaders and study participants. Further dissemination will be done through conference proceedings and publications. Trial registration number: Current Controlled Trials identifier: ISRCTN62041885 .